IMPROVING THE LEARNING OUTCOMES PASSING THE APPROACH TO PLAY VOLLEYBALL CREATIVE - Gery, Muhammad Ishaq (JOURNAL SPORTINDO, 2022)
This research aims to find out if through creative play can improve the outcome of learning passing a volley ball. The benefit of this research is to give educators an idea of the use of a suitable approach in teaching learning activities, so as to improve the quality of learning outcomes. The research action will be implemented two cycles, each cycle begins with planning, action, observation, and reflection. The subject of this study is a class VII E SMP Negeri 1 Seputih Agung which amounted to 34 people. Data collected from observation results and test results. The results showed that there was an increase in student learning outcomes, proven on the one-end cycle of learning to reach 19 students or 56% with an average value of 76. On cycles of two reaches 29 students or 85% with an average value of 83. In addition, with a creative play approach can improve students ' activity on the learning of passing over.